INFLUENCE OF ACADEMIC RESOURCE PROVIDER'S WORK ETHICS ON INSTITUTIONAL MANAGEMENT IN PUBLIC UNIVERSITY IN NYERI AND KIAMBU COUNTIES - Mathenge, Rosemary Wairimu; Chui, Dr. Mary Mugwe; Thinguri, Dr. Ruth (African Journal of Education and Practice, 2019)
Purpose: The purpose of this study was to investigate the influence of academic resource provider's work ethics on institutional management in public universities in Nyeri and Kiambu counties. The study was guided by the following research objective: to analyze the influence of the academic resource provider's work ethics on institutional management in public universities Methodology: Purposive sampling was used to select three universities based on their magnitude of part-time lecturers from which cluster sampling was used to select a sample size of 335 respondents. The study made use of questionnaires for Heads of departments and lecturers. Interview schedules for Deans and Human resource managers. In the piloting phase lecturers (12), Heads of departments (5), deans (2) and human resource manager (1) representing 1% of the target population to ensure the validity of the instruments and rater inter rater method was used to establish reliability. Concurrent triangulation was used to ensure credibility. Findings: The study confirmed that academic resource outsourcing influences institution management in public universities in Nyeri and Kiambu counties since selection satisfaction, quality of service, capability to handle and work ethics of the outsourced provider had significant influence on institution management.The investigation established that academic resource outsourcing was taking place in the public Universities in Kenya, and it had significant influence on institution management. Unique contributions to Theory, Practice and Policy: It is crucial for institutions to select qualified providers who have interest in learners' achievements. The study recommended that the government should put in place academic resource outsourcing guidelines.